Penguatan Budaya Lokal melalui Pemberdayaan Kelompok Pengrajin Angkinan Berbasis E-Commerce: Strengthening Local Culture through E-Commerce based Empowerment of Angkinan Craftsman Group - Yunisvita, Yunisvita; Andaiyani, Sri; Hidayat, Ariodillah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The Angkinan Craftsmen are included in homemade crafts, so the right strategy is needed to develop them. Applying this local culture is essential to the e-commerce business that can help increase Angkinan Craftsmen's income. This activity aims to assist in promoting products and provide training on the use of e-commerce applications. The method of implementing this service is training by providing counseling, tutorials, and discussions. The results show that the training participants can understand the importance of strengthening e-commerce-based local culture and apply online selling sites through Instagram and Shopee. It is very relevant to the current conditions where knowledge of the preferences and behavior of local shoppers is more dominant in online shopping using the most popular e-commerce applications. In this case, Angkinan embroidery artisans can provide detailed information regarding the products offered and how to interact with customers online. Without implementing local values, artisans will not have an effective go-to-market strategy and opportunities for embroidery artisans.